The courting of Bristol Keats [large type] - Pearson, Mary E. (Thorndike Press large print dynamic drama., 2024)
"When Bristol begins to receive letters from an 'aunt' she's never heard of, she reluctantly agrees to meet--and discovers that everything she thought she knew about her family is a lie. Even her father might still be alive, not killed but kidnapped by terrifying creatures and taken to a whole other realm--the one he is from. Pulled into a dangerous world of magic and intrigue, Bristol makes a deadly bargain with the fae leader, Tyghan. But what she doesn't know is that he is just as determined as she is to find her father--dead or alive"--